The Amazonian legend in English teaching: intercultural and linguistic aspects in designing a didactic sequence - Viani, Renan; Araújo, Clara Romana Costa; Hall, Silvia Cristina Barros de Souza (The ESPecialist, 2025)
This article aims to report and discuss the process of designing a didactic sequence for the textual genre legend, planned for English teaching in the Amazonian context. Grounded in Sociodiscursive Interactionism and Language Didactics, the study draws on Vygotskian, Voloshinovian/Bakhtinian, and Saussurean theoretical foundations, promoting dialogue with critical interculturality principles advocated in official documents (Brazil, 2018; Pará, 2021). The planning and construction process of the didactic sequence consisted of four phases: selecting the genre, studying the didactic model, planning the linguistic work (on lexical and morphosyntactic units), and developing the activities. Two types of instruments were proposed —the version framework and the opposition framework — to organize the planning of content and linguistic units, considering the relationship between context, genre, and intercultural strategies.